Company's Performance as A Variable Intervening Between Intellectual Capital and Company’s Value - Isna Ardila; Irma Christiana (Journal of International Conference Proceedings (JICP), 2019)
Intellectual capital is interpreted as intangible assets in the economy and the capital is assumed to be able to generate intellectual wealth. This paper investigates the influence of intellectual capital of the company's value with the company's performance as an intervening variable at the Jakarta Islamic Index in 2014-2017. Samples were taken using the purposive sampling method, obtained 8 companies as samples of the population as many as 30 companies. Sample data as much as 32 data. To analyze data using multiple linear regression, while to determine the influence of mediation using path analysis. The findings of this research that intellectual capital has no effect on the company's performance. The intellectual model, however, affects the value of the company by being mediated by the company's performance as a variable intervening.